Providing valid evidence for decision-making: the Drug Safety and Effectiveness Network Methods and Applications Group in Indirect Comparisons (DSEN MAGIC) - Sharon E. Straus; Brian Hutton; David Moher; Shannon E. Kelly; George A. Wells; Andrea C. Tricco (Canadian Science Publishing, 2022)
In 2009, the Canadian Institutes of Health Research, Health Canada, and other stakeholders established the Drug Safety and Effectiveness Network (DSEN) to address the paucity of information on drug safety and effectiveness in real-world settings. This unique network invited knowledge users (e.g., policy makers) to submit queries to be answered by relevant research teams. The research teams were launched via open calls for team grants focused in relevant methodologic areas. We describe the development and implementation of one of these collaborating centres, the Methods and Application Group for Indirect Comparisons (MAGIC). MAGIC was created to provide high-quality knowledge synthesis including network meta-analysis to meet knowledge user needs. Since 2011, MAGIC responded to 54% of queries submitted to DSEN. In the past 5 years, MAGIC produced 26 reports and 49 publications. It led to 15 trainees who entered industry, academia, and government. More than 10 000 people participated in courses delivered by MAGIC team members. Most importantly, MAGIC knowledge syntheses influenced practice and policy (e.g., use of biosimilars for patients with diabetes and use of smallpox vaccinations in people with contraindications) provincially, nationally, and internationally.